Micro-enterprises going global: Networks and institutional support in Poland - Belniak, Magdalena (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2026)
This article examines how Polish micro-enterprises internationalize under conditions of resource constraints in an increasingly digitalized environment. Micro-firms face structural limitations in financial, human, and managerial capacities, which challenge traditional incremental models of internationalization. The study aims to identify how collaborative networks, institutional support, and digital tools jointly influence the international expansion of micro-enterprises. The research adopts a mixed-methods approach, combining quantitative analysis of secondary data (Polish Agency for Enterprise Development, Eurostat, Global Entrepreneurship Monitor, Organisation for Economic Co-operation and Development) with qualitative case studies of three Polish micro-enterprises operating in e-commerce, ICT, and green technology sectors. The findings indicate that the complementarity of network embeddedness, institutional instruments, and digital capability primarily drives internationalization. Networks facilitate initial market access, institutional support reduces risk and enhances legitimacy, while digital tools accelerate and scale cross-border activities. The results suggest that micro-enterprise internationalization is better explained as a process of resource integration rather than gradual expansion, contributing to the literature on entrepreneurial internationalization in emerging EU economies.